Comparison of the impact of a system tele-antimicrobial stewardship program on the conversion of intravenous-to-oral antimicrobials in community hospitals - Brenda V. Maldonado Yanez; Kendall E. Ferrara; Richard Lueking; Taylor Morrisette; Erin E. Brewer; Nicole H. Lewis; Rachel Burgoon; Krutika Mediwala Hornback; Aaron C. Hamby (Cambridge University Press, 2024)
Abstract Objectives: Evaluate system-wide antimicrobial stewardship program (ASP) update impact on intravenous (IV)-to-oral (PO) antimicrobial conversion in select community hospitals through pre- and postimplementation trend analysis. Methods: Retrospective study across seven hospitals: region one (four hospitals, 827 beds) with tele-ASP managed by infectious diseases (ID)-trained pharmacists and region two (three hospitals, 498 beds) without. Data were collected pre- (April 2022-September 2022) and postimplementation (April 2023-September 2023) on nine antimicrobials for the IV to PO days of therapy (DOTs). Antimicrobial administration route and (DOTs)/1,000 patient days were extracted from the electronical medical record (EMR). Primary outcome: reduction in IV DOTs/1,000 patient days. Secondary outcomes: decrease in IV usage via PO:total antimicrobial ratios and cost reduction. Results: In region one, IV usage decreased from 461 to 209/1,000 patient days (P = < .001), while PO usage increased from 289 to 412/1,000 patient days (P = < .001). Total antimicrobial use decreased from 750 to 621/1,000 patient days (P = < .001). In region two, IV usage decreased from 300 to 243/1,000 patient days (P = .005), and PO usage rose from 154 to 198/1,000 patient days (P = .031). The PO:total antimicrobial ratios increased in both regions, from .42-.52 to .60-.70 in region one and from .36-.55 to .46-.55 in region two. IV cost savings amounted to $19,359.77 in region one and $4,038.51 in region two. Conclusion: The ASP intervention improved IV-to-PO conversion rates in both regions, highlighting the contribution of ID-trained pharmacists in enhancing ASP initiatives in region one and suggesting tele-ASP expansion may be beneficial in resource-constrained settings.